2023
DOI: 10.1007/s40136-023-00459-0
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Disparities in Otolaryngology

Abstract: Purpose of Review The purpose of this review is to summarize some of the recent research studies on healthcare disparities across various subspecialties within otolaryngology. This review also highlights the impact of COVID-19 pandemic on disparities and proposes potential interventions to mitigate disparities. Recent Findings Significant healthcare disparities in care and treatment outcomes have been reported across all areas of otolaryngology. Notable differences in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 147 publications
0
4
0
Order By: Relevance
“…Managing cancer care for patients with HNC and their families is challenging due to various obstacles, including delays in HNC referrals, diagnosis, treatment initiation, and postoperative radiation treatment delays, which are the only quality metric in head and neck oncology. 3 There is so much to learn about the barriers to and facilitators of timely HNC identified by Batool et al 2 A salient lesson from their study is the important role that nonotolaryngology clinicians (ie, dentists and primary care practitioners [PCPs]) have in the early diagnosis of HNC. Given that a universally approved method for screening asymptomatic individuals is lacking, dentists and PCPs are often the first to detect HNC-during routine checkups or when patients present with suggestive lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Managing cancer care for patients with HNC and their families is challenging due to various obstacles, including delays in HNC referrals, diagnosis, treatment initiation, and postoperative radiation treatment delays, which are the only quality metric in head and neck oncology. 3 There is so much to learn about the barriers to and facilitators of timely HNC identified by Batool et al 2 A salient lesson from their study is the important role that nonotolaryngology clinicians (ie, dentists and primary care practitioners [PCPs]) have in the early diagnosis of HNC. Given that a universally approved method for screening asymptomatic individuals is lacking, dentists and PCPs are often the first to detect HNC-during routine checkups or when patients present with suggestive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…and male and female otolaryngology−head and neck surgery faculty members (R.K.V.S., E.M.R., and R.W.B.). These guides, informed by the socioecological framework, aimed to explore barriers, facilitators, and improvement strategies in HNC referral pathways across individual, interpersonal, institutional, community, and policy levels . Before implementation, the guides were tested and 2 coauthors (S.B.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that due to climate changes and worsening air pollutions there is an increase of number of patients with exacerbate allergic rhinitis, asthma and other respiratory problems such as severe chronic rhinosinusitis. 5,6 Together with the number of patients, the hospitalization costs will grow. 7 Additionally, the problems associated with the ear, nose and throat (ENT) disease burden is largely underrecognized in social determinants of health.…”
Section: Introductionmentioning
confidence: 99%